Pengaruh Kualitas Pelayanan, Harga Dan Lokasi Terhadap Kepuasan Konsumen Pada Kedai Kopi Shelter Galunggung - Rangga Koswara; Ari Arisman; Suci Putri Lestari (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The research aims to analyze how much influence service quality, price and location have on consumer satisfaction. The research method used is a quantitative method. Quantitative analysis includes validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing through the T test and F test, as well as analysis of the coefficient of determination (R2). Effect of Service Quality, Price and Location on Consumer Satisfaction, the results showed with a coefficient value of 0.403 it can be seen that the service quality variable (X1), 0.433 is the price variable (X2) and 0.036 is the location variable (X3). Service quality (X1), price (X2) and location (X3) which have a strong relationship to customer satisfaction can be seen in the R Square value of 0.472, which indicates that the independent variables consisting of service quality, price and location can be explained by customer satisfaction 47.2% were able to explain the dependent variable, namely consumer satisfaction (Y) while the remaining 52.8% is influenced by other variables not examined in this research. The conclusion of this study is that service quality and price have a significant effect on consumer satisfaction at the Galunggung Shelter Coffee Shop, while location also has a significant effect on customer satisfaction.